Comparison of tendon suture fixation and cortical screw fixation for treatment of distal tibiofibular syndesmosis injury: A case-control study. Issue 34 (21st August 2020) - Song, Liuhong; Liao, Zhifu; Kuang, Zhongqiang; Qu, Shiyan; Zhang, Wei; Yuan, Yang; Fang, Teng
Abstract : Abstract: This study aimed to investigate the effectiveness of tendon suture fixation versus cortical screw fixation for the treatment of distal tibiofibular syndesmosis injury. This study recruited 42 patients with Danis-Weber type B, C1 and C2 fractures concomitant with lower tibiofibular syndesmosis injury, who were randomly assigned to 2 groups according to treatment with cortical screw fixation (n = 21) and tendon suture fixation (n = 21). Operation time, intraoperative blood loss, time to full weight-bearing activity, medical cost, ankle function, and ankle pain were compared between the 2 groups. The operation time was significantly less with cortical screw fixation (57.1 ± 5.3 min) than with tendon suture fixation (63.3 ± 6.3 min; p = 0.01), but there was no significant difference in intraoperative blood loss. The time until full weight-bearing was possible was significantly longer after cortical screw fixation (10.9 ± 2.7 weeks) than after tendon suture fixation (7.1 ± 1.9 weeks; P < .001). The medical cost was much greater for cortical screw fixation (1861.6 ± 187.3 USD) than for tendon suture fixation (1209.6 ± 97.6 USD; P < .01). The rate of excellent and good ankle function at 3 months after surgery was significantly higher with tendon suture fixation (71.4%) than with cortical screw fixation (33.3%; P = .03). Tendon suture fixation is associated with quicker recovery of ankle function, shorter time to full weight-bearing, and lower medical cost to the patient compared with screw fixation. Our findings suggest that tendon suture fixation is an effective method for the treatment of tibiofibular syndesmosis injury.